Dynamic Style Preferences of Individual Investors and Stock Returns - Kumar, Alok (Journal of Financial and Quantitative Analysis, 2009)
Abstract This study shows that individual investors systematically shift their preferences across extreme style portfolios (small vs. large, value vs. growth). These preference shifts are influenced by past style returns and earnings differentials, and advice from investment newsletters, but are unaffected by innovations in macroeconomic variables or shifts in expectations about future cash flows. Furthermore, investors’ dynamic style preferences influence returns along multiple dimensions: i) the contemporaneous relation between style returns and style-level preference shifts is strong, ii) there is weak evidence of style return predictability, and iii) the correlations among stocks within a style increase when investors move into or out of the style with greater intensity. Overall, the results indicate that stock categorization influences investors’ portfolio decisions and stock returns.